2013
DOI: 10.1128/jvi.00996-13
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Feline Immunodeficiency Virus Directly Activates CD4 + CD25 + T Regulatory Cells

Abstract: Lentivirus infection activates CD4؉ CD25 ؉ T regulatory (Treg) cells. Activation of Treg cells may be due to direct virus infection or chronic antigenic stimulation. Herein we demonstrate that in vitro feline immunodeficiency virus (FIV) infection, but not UV-inactivated virus, activates Treg cells as measured by immunosuppressive function and upregulation of GARP, FoxP3, and membrane-bound transforming growth factor ␤ (TGF-␤). These data demonstrate for the first time that AIDS lentiviruses infect and activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Among the many achievements, these efforts led to approval of an effective FIV vaccine in 2002. Recent studies have addressed important issues such as mechanisms of FIV transmission, replication and evolution [ 22 , 23 , 24 , 25 , 26 , 27 ], FIV vaccine efficacy [ 28 , 29 ], the role of neutralizing antibodies in disease progression [ 28 , 30 , 31 ], virus assembly and release [ 32 , 33 ], viral latency and eradication strategies [ 34 , 35 , 36 ], development of adjunctive therapies [ 37 , 38 , 39 , 40 ], immunology [ 41 , 42 , 43 , 44 , 45 ], interactions with the microbiome [ 46 , 47 ], development of antiretroviral compounds [ 48 , 49 , 50 ] and development of protocols for assessing feline cognitive function [ 51 , 52 , 53 , 54 ]. Many of these efforts are summarized in this volume and in a review by Bienzle [ 55 ].…”
Section: Fiv Infection Of the Nervous Systemmentioning
confidence: 99%
“…Among the many achievements, these efforts led to approval of an effective FIV vaccine in 2002. Recent studies have addressed important issues such as mechanisms of FIV transmission, replication and evolution [ 22 , 23 , 24 , 25 , 26 , 27 ], FIV vaccine efficacy [ 28 , 29 ], the role of neutralizing antibodies in disease progression [ 28 , 30 , 31 ], virus assembly and release [ 32 , 33 ], viral latency and eradication strategies [ 34 , 35 , 36 ], development of adjunctive therapies [ 37 , 38 , 39 , 40 ], immunology [ 41 , 42 , 43 , 44 , 45 ], interactions with the microbiome [ 46 , 47 ], development of antiretroviral compounds [ 48 , 49 , 50 ] and development of protocols for assessing feline cognitive function [ 51 , 52 , 53 , 54 ]. Many of these efforts are summarized in this volume and in a review by Bienzle [ 55 ].…”
Section: Fiv Infection Of the Nervous Systemmentioning
confidence: 99%
“…Previous reports have demonstrated that various viruses may take advantage of host immune mechanisms associated with immunosuppressive functions to aid viral expansion and contribute to viral pathophysiology [ 12 ]. Viral infection can induce CD25 expression in lymphocytes [ 13 ] or directly activate CD4+CD25+ cells, potentially contributing to immune dysfunction [ 14 ]. Expanded Treg populations have been detected in many virus-related diseases, such as those caused by hepatitis C virus [ 15 , 16 , 17 ], hepatitis B virus [ 18 , 19 ], Epstein-Barr virus [ 20 ], and porcine reproductive and respiratory syndrome virus [ 21 ], as well as upon secondary infection with a virus [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Foxp3 mRNA and protein are increased in lentivirus activated Treg cells when compared to Treg cells from uninfected cats [ 8 , 26 ]. To document increased Foxp3 expression in Treg cells for these studies, we harvested peripheral blood Treg cells from FIV − control cats and FIV + cats 1 week, 4 weeks, 8 weeks and 24 weeks post infection (p.i.)…”
Section: Resultsmentioning
confidence: 99%